1998
DOI: 10.1074/jbc.273.45.29577
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor α-Isoform Deficiency Leads to Progressive Dyslipidemia with Sexually Dimorphic Obesity and Steatosis

Abstract: The ␣-isoform of the peroxisome proliferator-activated receptor (PPAR␣) is a nuclear transcription factor activated by structurally diverse chemicals referred to as peroxisome proliferators. Activators can be endogenous molecules (fatty acids/steroids) or xenobiotics (fibrate lipid-lowering drugs). Upon pharmacological activation, PPAR␣ modulates target genes encoding lipid metabolism enzymes, lipid transporters, or apolipoproteins, suggesting a role in lipid homeostasis. Transgenic mice deficient in PPAR␣ wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
251
3
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(279 citation statements)
references
References 66 publications
23
251
3
2
Order By: Relevance
“…Interactions with sex have been reported previously from studies of Finnish 54 and Norwegian 55 twins, from a segregation analysis of the Québec Family Study, 56 and from studies of inbred rat strains that have found sex-specific QTLs for obesity. 57 Sexual dimorphism has also been observed in such characteristics as leptin concentration and ob gene expression; 58 expression of hormone-sensitive lipase and lipoprotein lipase in subcutaneous abdominal fat in response to weight loss; 59 fat deposition in PPAR-a knockout mice; 60 the effect of variants in the leptin receptor, 61 and in the leptin gene itself. 62 While it is important to determine whether sex-specific QTLs for adiposity replicate in other studies, our results suggest that sex may have important environmental influences and that our ability to identify relevant genes may be improved by incorporating such effects into our linkage models.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with sex have been reported previously from studies of Finnish 54 and Norwegian 55 twins, from a segregation analysis of the Québec Family Study, 56 and from studies of inbred rat strains that have found sex-specific QTLs for obesity. 57 Sexual dimorphism has also been observed in such characteristics as leptin concentration and ob gene expression; 58 expression of hormone-sensitive lipase and lipoprotein lipase in subcutaneous abdominal fat in response to weight loss; 59 fat deposition in PPAR-a knockout mice; 60 the effect of variants in the leptin receptor, 61 and in the leptin gene itself. 62 While it is important to determine whether sex-specific QTLs for adiposity replicate in other studies, our results suggest that sex may have important environmental influences and that our ability to identify relevant genes may be improved by incorporating such effects into our linkage models.…”
Section: Discussionmentioning
confidence: 99%
“…However, these animals display spontaneous, sexually dimorphic, late onset obesity (despite stable caloric intake) which is associated with adipocyte hypertrophy [91]. Furthermore, they are prone to diet-induced obesity which paradoxically is associated with enhanced insulin sensitivity [92].…”
Section: Pparmentioning
confidence: 99%
“…Male PPAR-null mice on a C57BL/6J genetic background [36,37], and aged-matched wildtype counterparts (Charles River, Les Oncins, France; 4 weeks acclimatization) were housed in polycarbonate cages at 22 + 2°C on a 12 hour light/dark cycle and allowed free access to water and food. In vivo studies were conducted under European Union Guidelines for the use and care of laboratory animals and were approved by an independent ethics committee.…”
Section: Animals and Maintenancementioning
confidence: 99%